Dynamic postural stability, is associated with competitive level, in youth league soccer players - Pau, M.; Porta, M.; Arippa, F.; Pilloni, G.; Sorrentino, M.; Carta, M.; Mura, M.; Leban, B. (Physical Therapy in Sport, 2019)
Objectives: To assess the effect of competitive level on dynamic postural stability in young elite and subelite soccer players. Design: Cross-sectional study. Setting: Laboratory. Participants: Fifty-four male soccer players of Under 16 and Under 17 categories (mean age 15.9 ± 0.6), divided into two groups who regularly compete at national (n ¼ 28) and regional (n ¼ 26) levels. Main outcome measures: Dynamic Postural Stability Index (DPSI) and vertical Time to Stabilization (vTTS) for a forward-jump landing. Static postural sway was calculated on the basis of center-of-pressure trajectories for a 20 s one-legged stance. Results: Players at national level exhibit better dynamic postural control than those at regional level, as indicated by the significantly lower DPSI (0.327 vs. 0.373, p < 0.001) and vTTS (0.887 vs. 1.158 s, p ¼ 0.003). In contrast, no differences between groups were found in any of the postural sway parameters for the static test. Conclusions: Young soccer players at national level are characterized by better balance performance in terms of faster and more efficient stabilization after a forward jump, while one-leg static standing tests appear not challenging enough to reveal differences in balance abilities associated with the combination of superior technical and physical features.